Non-Mutually Exclusive Trade-off and Pecking Order Theories: A Study in Indonesia - Pamungkas, Wihandaru Sotya; Surwanti, Arni (Universitas Muhammadiyah Yogyakarta, 2021)
Research aim: This study aimed to strengthen empirical evidence that the trade-off (TOT) and pecking order (POT) theories in Indonesia are non-mutually exclusive.Design/methodology/approach: This study employed a sample of 636 manufacturing companies from 2014 to 2018.Research finding: The results revealed that companies in Indonesia used a Capital Structure consistent (CS) with the TOT and POT, or in other words, the TOT and POT theories are non-mutually exclusive.Theoretical contribution/originality: This study is different from previous research on data analysis strengthened by separating underleveraged and overleveraged companies.Practitioner/Policy implication: CS in Indonesia is following the TOT if it is underleveraged and according to POT if it is overleveraged.Research limitation/implication: This study has the limitation of only using a sample of manufacturing companies in Indonesia. Subsequent research can provide comprehensive results by increasing the sample of all companies excludes the financial sector.